2005
DOI: 10.1088/1367-2630/7/1/072
|View full text |Cite
|
Sign up to set email alerts
|

Control of the entanglement of two atoms in an optical cavity via white noise

Abstract: Two two-level atoms within a leaky optical cavity is driven by two independent external optical white noise fields. We investigate how entanglement between two atoms arises in such a situation. The steady state entanglement of two atoms is also investigated. A stochastic-resonance-like behavior of entanglement is revealed. Finally, the Bell violation between atoms is discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…This result has already been pointed out in the literature [25,27], however, let us insist on the fact that, it is not the amount of decoherence induced on the qubits by their environments what destroys entanglement, but their similarity in nature (or temperatures in the case of thermal baths). Let us then consider the cases with r 2 < r 1 in the rest of this section.…”
Section: Entanglement and Linear Entropymentioning
confidence: 70%
See 1 more Smart Citation
“…This result has already been pointed out in the literature [25,27], however, let us insist on the fact that, it is not the amount of decoherence induced on the qubits by their environments what destroys entanglement, but their similarity in nature (or temperatures in the case of thermal baths). Let us then consider the cases with r 2 < r 1 in the rest of this section.…”
Section: Entanglement and Linear Entropymentioning
confidence: 70%
“…Xu and Li [25] found that with two equally intense white-noise sources at the same temperature, no entanglement can be formed in the steady state. However, if only one qubit was subjected to a finite temperature source, some entanglement could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [22,23], it has been shown that white noise may play a positive role in generating the controllable entanglement in some specific conditions. Malinovsy and Sola [24] have proposed a method of controlling entanglement in a two-qubit system by changing a relative phase of the pulses.…”
Section: Introductionmentioning
confidence: 99%
“…In most treatments the entanglement resulted from the direct interaction between the atoms or has been created by engineering the interaction through the couphng of the atoms to the same cavity mode [3,4,5,6,7]. Entanglement between atoms trapped inside an optical cavity is usually studied for an idealized model of the atoms located precisely at the antinodes of the cavity field.…”
Section: Introductionmentioning
confidence: 99%